Neural Representations of Task Context and Temporal Order During Action Sequence Execution. (9th April 2021) - Shahnazian, Danesh; Senoussi, Mehdi; Krebs, Ruth M.; Verguts, Tom; Holroyd, Clay B.
Abstract: Routine action sequences can share a great deal of similarity in terms of their stimulus response mappings. As a consequence, their correct execution relies crucially on the ability to preserve contextual and temporal information. However, there are few empirical studies on the neural mechanism and the brain areas maintaining such information. To address this gap in the literature, we recently recorded the blood‐oxygen level dependent (BOLD) response in a newly developed coffee–tea making task. The task involves the execution of four action sequences that each comprise six consecutive decision states, which allows for examining the maintenance of contextual and temporal information. Here, we report a reanalysis of this dataset using a data‐driven approach, namely multivariate pattern analysis, that examines context‐dependent neural activity across several predefined regions of interest. Results highlight involvement of the inferior‐temporal gyrus and lateral prefrontal cortex in maintaining temporal and contextual information for the execution of hierarchically organized action sequences. Furthermore, temporal information seems to be more strongly encoded in areas over the left hemisphere. Abstract : Routine action sequences critically rely on neural mechanisms maintaining contextual and temporal information to disambiguate similar tasks (e.g. making coffee or tea). In this study we show the involvement of areas in temporal and lateral prefrontal cortices in maintaining temporal and contextual information for the execution of hierarchically‐organized action sequences.